Structural and lectin-detectable changes of liver induced by a long-term administration of antihistamine agent Loratadine (Journal of Medical Science, 2016)
Adverse effects of pharmacological agents are currently under considerable attention of theoretical and clinical medicine. The aim of present investigation was to study in experiment the effect of a long-term administration of antihistamine drug Loratadine on the micromorphology and carbohydrate determinants of the liver. Experimental rats once a day during 30 days intragastrically received Loratadine in the form of an aqueous suspension in the dose of 0.15 mg/kg body weight. On days 10, 30, 40, 50, 60 of experiment euthanasia was carried out, liver samples excised, fixed in 4% formaline and embedded in paraffin. Examination of haematoxylin and eosin stained sections revealed extension of sinusoid capillaries and central veins, granular dystrophy of hepatocytes supplemented with perivascular lymphoid infiltration, these phenomena receiving highest development on days 30th and 40th of experiment. At the same times PAS reaction demonstrated increased content of glycogen deposits in hepatocytes, apparently encompassing alterations in glucose metabolism. On the later stages of experiment (days 20th and 30th after the last Loratadine injection) signs of hepatocyte alteration decreased significantly, and content of glycogen returned to normal values. Loratadine administration induced the accumulation in the intra- and 2 perisinusoidal space of hepatic lobules of activated Kupffer cells, which were strongly PAS- and WGA-positive, as well as the enhanced exposure of DGlcNAc and DGalNAc determinants by glycoconjugates in within the altered hepatocytes. Our results indicate certain destructive effect of Loratadine on hepatic micromorphology and function; the cessation of this drug administration was accompanied by simultaneous strengthening of regenerative processes.